Developing an Instrument for Measurement of Attitude toward Online Shopping - Delafrooz, Narges; Paim, Laily; Khatibi, Ali (Eurojournals, 2009)
To ensure the success of online business, it is important for the retailers to understand their targeted customers. The aim of this study is to develop an instrument for investigating and understanding consumer’s online shopping orientations and factors that influence attitude toward online shopping and online shopping intention. A five-level Likert scale was used to determine attitude toward online shopping. A self-administered questionnaire, based on prior literature, was developed, and a total of 370 post graduate students of University Putra Malaysia were selected by random sampling and involved in the study. Eight components, referring to online shopping orientation and online shopping perceived benefits, were found to explain 97 % of the variability in consumer’s online shopping orientation. They were subsequently labeled: utilitarian online shopping orientation, hedonic online shopping orientation, fun, convenience, customer service, homepage, wider selection and price. The reliability of data and scale was tested by computing Cronbach’s Alpha. Alpha values were 0.874 for online shopping orientation, 0.921 for perceived benefits, and 0.853 for attitude. These alpha values exceed the 0.80 recommended acceptable inter-items reliability threshold, indicating a high correlation among the variables comprising the set, and accordingly, that individual items (or sets of items) should produce results consistent with the overall instrument. In light of this, this instrument is offered to the research community as a tool that may be used in conducting future research related to online shopping behavior.